Photons fluence to local skin Dose coefficients and benchmark with three Monte-Carlo codes. Application to the computation of radioactive material transport limits. (October 2021) - Frosio, Thomas; Bertreix, Philippe; Menaa, Nabil; Thomas, Samuel; Eberhardt, Holger; Endres, Janis
Abstract: Fluence to Local Skin Dose Conversion Coefficients (LSD-CC) are radiological protection quantities used for external radiation exposures which allow the conversion of particle fluences into local skin equivalent dose. The International Commission on Radiological Protection published LSD-CC for electrons with an energy range from 10 keV to 10 MeV. However, the literature does not address these radiation protection quantities for all particle types, in particular for photons. In this article, computed LSD-CC values for photons are presented which enrich the literature and are of interest for the radiation protection community. As an example for an application of the use of the computed LSD-CC values, the IAEA A1/A2 working group, which supports the review of the international regulation related to the transport of radioactive material, has decided to estimate the dose to the skin using such coefficients. In this publication, LSD-CC for photons are computed and benchmarked using GEANT4, FLUKA and MCNP. In addition, the FLUKA Monte-Carlo calculation code is used to compute the LSD-CC values for electrons and positrons to compare with existing data in the literature and validate the presented models. As one application of these LSD-CC values, the transfer functions for calculating the IAEA A-values are determined using the LSD-CC and are compared to a one-step direct calculation method. Highlights: Computation of Fluence to Local Skin Dose coefficients for photons . Benchmark between GEANT4, MCNP and FLUKA . Application to compute quantity for the new transport regulation of radioactive material .